Peranan Penyuluh Pertanian Dalam Pengembangan Kelompok Tani Di Desa Sungai Binuang Kecamatan Haur Gading Kabupaten Hulu Sungai Utara - Azwar Saihani; Siti Noor Asiah Jamil (Rawa Sains: Jurnal Sains STIPER Amuntai, 2017)
This study aims to identify the role of extension agents in developing farmer groups in Sungai Binuang Village, Haur Gading District, as well as how the current authority and competence of extension agents to farmer groups. This research was conducted in Sungai Binuang Village, Haur Gading Sub-District in March-May 2016. The samples taken in this study were all members of farmer groups in Sungai Binuang Village. The analysis method used in this study is descriptive analysis and Likert scale for measuring indicators. the role of extension agents as farmer supervisors is at an average number of 287 in the good interval category with a number of 76.5% classified as strong, as an organizer and dynamist the instructor is at an average rate of 306 in a very good area with 81.6% classified as very strong , as a technician the extension has an average number of 306 in the area is very good and 81.6% is classified as very strong, and the extension agent as a farmer consultant that is 306.5 in the area very well and continuum 81.7% at very strong intervals . From the results of the study, it was found that the role of agricultural extension agents in Sungai Binuang Village was already quite optimal. The authority and competence of agricultural extension agents cannot be done optimally because an agricultural instructor is only authorized to direct and provide input on all decisions taken in a group